Tuberculin Skin Testing in Children - Reznik, Marina (Centers for Disease Control and Prevention, 2006)
In 1996, the American Academy of Pediatrics (AAP) recommended targeted tuberculin skin testing (TST) of children while discouraging routine TST of children without risk factors for tuberculosis (TB). Recent studies have provided evidence in support of the targeted TST and recommendations that favor risk assessment over universal screening with TST. While evidence for targeted TB testing exists and benefits of screening programs are clear, administrative logistics could be a greater issue. The challenge for public health and school officials is to develop a screening program that avoids stigmatization of the at-risk group. Until then, pediatric healthcare providers will continue to have a key role in identifying children at risk for latent TB infection by using the AAP-endorsed risk-assessment questionnaire and should screen children with TST only when >1 risk factor is present.